Co-seismic deformation of the 2017 Ms 7.0 Jiuzhaigou Earthquake observed with GaoFen-3 interferometry. Issue 17 (1st September 2020) - Chen, Xue; Peng, Junhuan; Motagh, Mahdi; Zheng, Yueze; Shi, Mengyao; Yang, Honglei; Jia, Qingren
ABSTRACT: The first application of GaoFen-3 synthetic aperture radar (SAR) interferometry to monitoring co-seismic deformation of an earthquake is presented in this paper. First, two GaoFen-3 SAR images spanning the 2017 surface-wave magnitude ( M s ) 7.0 Jiuzhaigou earthquake were mosaicked, coregistered and processed into an interferogram with visible fringes. After the removal of severe orbital errors and unwrapping, the co-seismic deformation field is obtained. Finally, the fault parameters and slip distribution are determined based on the deformation field. To evaluate the performance of GaoFen-3 in this case, the interferogram, co-seismic deformation field, derived fault parameters and slip distribution are compared with those derived from Radarsat-2, Sentinel-1A and Advanced Land Observing Satellite-2 (ALOS-2) Phased Array type L-band Synthetic Aperture Radar-2 (PALSAR-2). The comparisons between the deformation field obtained from GaoFen-3 and those obtained from Radarsat-2 and Sentinel-1A show Pearson's correlation coefficient ( r ) values > 90%, demonstrating that GaoFen-3 interferometry can measure the co-seismic deformation effectively. The resultant slip model obtained by GaoFen-3 interferometric measurements shows a simple, elliptical pattern of slip, reaching a maximum of approximately 1 m at depths of 10–13 km. The rake angle is almost 0 ∘, which suggests left-lateral strike-slip motion, consistent with previous studies.